Proceso de atención de enfermería en gestante de 37 años con preeclampsia severa. - Barragán Mancheno, Grace Dayanara (2020)
Preeclampsia is one of the main complications during pregnancy and its prevalence rate ranges from 1.8% to 16.7%, the origin of this pathology during pregnancy is still unknown however it is related to the main health problems that can compromise the life of both the mother and the baby. Among the characteristics of preeclampsia is the existence ofl endothelial damage, increased sensitivity to circulating pressurized substances, accompanied by ischemia, necrosis and coagulopathy, pregnancy-induced hypertension (preeclampsia) is a particularity of human pregnancy, characterized by the increase in blood pressure of 140/90 mm Hg or higher, which occurs approximately from 20 weeks during pregnancy,the appropriate management of the delivery period are the most effective measures to reduce mortalityproduced by this cause. This study, revealing a 37-year-old female patient in a 10-week pregnant state who was diagnosed with preeclampsia, has no family history, enters the hospital for presenting a hypertensive picture accompanied by high-intensity headache with an assessment on the Eva 10/10 scale, plus lower limb oedema and unquantified fluid loss of approximately 9 hours of evolution.